2020
DOI: 10.1097/md.0000000000020065
|View full text |Cite
|
Sign up to set email alerts
|

Soluble PD-L1: a potential immune marker for HIV-1 infection and virological failure

Abstract: Despite viral control, basal chronic inflammation and its related comorbidities remain unsolved problems among HIV-infected individuals. Soluble factors derived from myeloid cells have emerged as potent markers associated with HIV-related comorbidities and mortality. In the present report, we explored the relationship between soluble programmed death-ligand 1 (sPD-L1) and HIV-1 infection, antiretroviral therapy (ART), CD4/CD8 ratio, viral load (VL), and sexually transmitted coinfections. A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
11
0
1
Order By: Relevance
“…To explore the origin of these differences, we studied soluble factors associated with immune cell exhaustion and immunosenescence. All MS patients showed a modest age-associated increase of PD-L1, a check point molecule capable of inducing T cell tolerization that rises in old individuals ( 29 ). This confirms the appearance of an early immunosenescence process in MS patients, since this study was performed in individuals aged between 16 and 65 years, an age at which most healthy individuals did not enter in the immunosenescence process yet.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the origin of these differences, we studied soluble factors associated with immune cell exhaustion and immunosenescence. All MS patients showed a modest age-associated increase of PD-L1, a check point molecule capable of inducing T cell tolerization that rises in old individuals ( 29 ). This confirms the appearance of an early immunosenescence process in MS patients, since this study was performed in individuals aged between 16 and 65 years, an age at which most healthy individuals did not enter in the immunosenescence process yet.…”
Section: Discussionmentioning
confidence: 99%
“… [ 136 , 137 ] HIV-1 infection (AIDS) Much higher levels of sPD-L1 in HIV-infected patients compared to uninfected adults. [ 138 , 139 ] Acute respiratory distress syndrome (ARDS) sPD-L1 upregulated in survivors of direct ARDS compared to non-survivors. sPD-L1 induces apoptosis of monocyte-derived macrophages in ARDS patients.…”
Section: Soluble Pd-l1 Beyond Cancermentioning
confidence: 99%
“…Moreover, the levels of sPD-L1 were also high in individuals that do not respond to antiretroviral therapy. The circulating protein may thus be particularly useful to follow the treatment response in HIV patients [ 138 ]. In HIV-positive patients, the high level of sPD-L1 likely arises from mPD-L1 expressed on monocyte-derived dendritic cells, which at the same time present an elevated level of MMP-2, susceptible to produce sPD-L1 upon proteolysis [ 139 ].…”
Section: Soluble Pd-l1 Beyond Cancermentioning
confidence: 99%
“…A recent study used ELISA to quantify plasma levels of sPD-L1 in PLHIV and healthy controls and found that plasma levels of sPD-L1 were significantly elevated in PLHIV and remained high despite control of HIV infection by ART 107 . In addition, PLHIV on ART with virological failure had the highest plasma levels of sPD-L1 107 . Thus, sPD-L1 in the peripheral blood represents a potential biomarker of immune exhaustion and virological failure in PLHIV.…”
Section: Soluble Immune Checkpoints In People Living With Hiv (Plhiv)mentioning
confidence: 99%
“…In addition to mICPs that have been demonstrated to play a critical role in immune homeostasis in PLHIV, sICPs may also be dysregulated in PLHIV and thereby contribute to immune exhaustion in PLHIV. A recent study used ELISA to quantify plasma levels of sPD-L1 in PLHIV and healthy controls and found that plasma levels of sPD-L1 were significantly elevated in PLHIV and remained high despite control of HIV infection by ART 107 . In addition, PLHIV on ART with virological failure had the highest plasma levels of sPD-L1 107 .…”
Section: Introductionmentioning
confidence: 99%